2009
DOI: 10.1159/000224636
|View full text |Cite
|
Sign up to set email alerts
|

Genome Scan, Fine-Mapping, and Candidate Gene Analysis of Non-Syndromic Cleft Lip with or without Cleft Palate Reveals Phenotype-Specific Differences in Linkage and Association Results

Abstract: Objectives: Non-syndromic orofacial clefts, i.e. cleft lip (CL) and cleft palate (CP), are among the most common birth defects. The goal of this study was to identify genomic regions and genes for CL with or without CP (CL/P). Methods: We performed linkage analyses of a 10 cM genome scan in 820 multiplex CL/P families (6,565 individuals). Significant linkage results were followed by association analyses of 1,476 SNPs in candidate genes and regions, utilizing a weighted false discovery rate (wFDR) approach to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
4
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 192 publications
9
121
4
6
Order By: Relevance
“…Thus, our study and other studies (Marazita et al. 2009; Dixon et al. 2011) presuppose the need to carry out deep subclinical phenotyping in families with history of clefts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study and other studies (Marazita et al. 2009; Dixon et al. 2011) presuppose the need to carry out deep subclinical phenotyping in families with history of clefts.…”
Section: Discussionmentioning
confidence: 99%
“…Murray 10 and Grosen et al 11 found heritability estimates exceeding 90% for CLP phenotypes. Genetic studies including linkage analysis 12,13 , genome-wide association, and GWASbased meta-analysis 14 , have yielded reproducible evidence for several genes and gene regions 8 . Results from Ludwig et al…”
Section: Genetic Factors and Nsclpmentioning
confidence: 99%
“…But, although many of these signals have been replicated in independent samples, several of the linkage regions are broad and the underlying causal gene(s) are poorly established. Incomplete knowledge about gene function presents difficulties for selecting the most likely 12 have not replicated subsequently in independent samples 13 . Successful replication is difficult to achieve and it is perhaps too early to dismiss some of the more uncertain signals.…”
Section: Genetic Factors and Nsclpmentioning
confidence: 99%
“…ARDINGER et al, 1989;MARAZITA et al, 2009;MORENO et al, 2009;VIEIRA et al, 2005). On the other hand, common variants conferring susceptibility to NSCL/P have been mostly identified by Genome-Wide Association Studies (GWAS) and the most replicated genomic region lies in a gene desert at 8q24.21, in which rs987525 emerges as the most significant SNP, including in the Brazilian population .…”
Section: Discussionmentioning
confidence: 99%